Fabrication and properties of YBa2Cu3O7-x ceramics at different sintering temperatures - Poom Prayoonphokkharat (2018)
The influence of sintering temperatures on the fabrication of YBCO ceramics under normal air atmosphere was investigated in this study. YBCO ceramics were prepared by mixing starting compounds of Y 2 O 3 , BaCO 3 and CuO powders, which were calcined at 850°C for 12 h. The powder was pelletized and sintered at different temperatures, from 930°C-1050°C, for 12 h. Phase identification was carried out by x-ray diffraction (XRD) technique. Scanning electron microscopy (SEM) with energy dispersive x-ray analysis (EDS) was used to study microstructure and chemical composition. In addition, density, Vickers hardness properties, the change of resistance and dielectric properties with temperature above T c were investigated. It was found that, at 950°C-1000°C, high-purity YBCO ceramic could be obtained. Outside this temperature range, either impurity phases were present or melting occurred. SEM images showed that grain size, which ranged from 1.5-2.5 μm, and hardness were related to density and liquid phase present in the sample. Furthermore, the sintering temperature affected oxygen content which, in turn, determined the conductive or semi-conductive behavior observed by electrical property measurement. © 2013 The Korean Institute of Metals and Materials and Springer Science+Business Media Dordrecht.